2012
DOI: 10.1186/1746-6148-8-52
|View full text |Cite
|
Sign up to set email alerts
|

Non-tuberculous mycobacteria isolated from slaughter pigs in Mubende district, Uganda

Abstract: BackgroundThe importance of infections caused by non-tuberculous mycobacteria (NTM) in animals and humans has gained considerable recognition during the past few years. In the developed world, where pig production is extensively practiced, studies on mycobacterial infections and related control strategies have received increasing attention. The infections are reported to be caused by a wide spectrum of NTM. Unfortunately, these infections have been less recognized in sub-Saharan Africa owing to lack of awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
7
17
0
Order By: Relevance
“…It should be kept in mind that Mycobacteria also could be detected in ICLN groups other than granulomatous ICLNs in very low abundance, indicating a risk even if no granulomatous pathology can be observed in ICLNs. A similar observation was recently described in a study where 31% of Mycobacterium-positive lymph nodes of slaughter pigs did not show any visible lesions (56). This is interesting, considering that Mycobacteria are usually diagnosed only during postmortem examination in the slaughter process (57,58).…”
Section: Discussionsupporting
confidence: 62%
“…It should be kept in mind that Mycobacteria also could be detected in ICLN groups other than granulomatous ICLNs in very low abundance, indicating a risk even if no granulomatous pathology can be observed in ICLNs. A similar observation was recently described in a study where 31% of Mycobacterium-positive lymph nodes of slaughter pigs did not show any visible lesions (56). This is interesting, considering that Mycobacteria are usually diagnosed only during postmortem examination in the slaughter process (57,58).…”
Section: Discussionsupporting
confidence: 62%
“…Routine abattoir meat inspections is the only economically feasible food safety tool that can be used in resource limited settings [10], however routine inspection is reported to have a low sensitivity for detecting tuberculosis lesions [16,17]. A recent study on slaughter pigs in Uganda also revealed that up to 31% of slaughtered pigs without visible lesions were harbouring non-tuberculous mycobacteria [18]. The sensitivity of routine inspection is reported to be affected by the frequency, dispersion and size of the lesions in addition to abattoir-environment factors like lighting and speed of flow system [19].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have characterised isolates of M. bovis from cattle and humans in the cattle corridor, revealing identical spoligotypes [22,23]. There are reports documenting the prevalence of non-tuberculous mycobacteria from slaughtered pigs in the Mubende district [18,24], but the role of pigs in the epidemiology of M. bovis had not been explored. This study was thus aimed at contributing to the knowledge of the epidemiology of M. bovis infections in Uganda, by investigating the occurrence and molecular characteristics of M. bovis from slaughter pigs, and by comparing these isolates with M. bovis detected from humans and cattle in earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…M. asiaticum has been isolated in monkeys (3) and pigs (4). In humans, M. asiaticum isolates have been obtained from respiratory tract specimens (5, 6), lyphadenitis, bursitis, and wound specimens (7), and keratitis samples (8).…”
Section: Genome Announcementmentioning
confidence: 99%